Moxifloxacin and bilateral acute iris transillumination - Knape, Robert M (Springer, 2013)
Recent publications have alerted clinicians to a syndrome of uveitic transilluminating iris depigmentation associated with systemic fluoroquinolones and other antibiotics. Bilateral acute iris transillumination, which is associated with loss of the iris pigment epithelium and results in iris transillumination, differs from the previously described bilateral acute depigmentation of the iris, which is associated with atrophy of the iris stroma without transillumination. We present a case of fluoroquinolone-associated uveitis with anterior segment optical coherence tomography imaging to highlight some observations about this syndrome. We interpret pharmacokinetic data to help explain why oral, but not topical, moxifloxacin may cause fluoroquinolone-associated uveitis.